2018
DOI: 10.1016/j.ultsonch.2017.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted extraction of rare-earth elements from carbonatite rocks

Abstract: In view of the increasing demand for rare-earth elements (REE) in many areas of high technology, alternative methods for the extraction of these elements have been developed. In this work, a process based on the use of ultrasound for the extraction of REE from carbonatite (an igneous rock) is proposed to avoid the use of concentrated reagents, high temperature and excessive extraction time. In this pioneer work for REE extraction from carbonatite rocks in a preliminary investigation, ultrasonic baths, cup horn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…A thermodynamic study, in the form of species distribution diagrams using the Hydra-Medusa software suite [21] was performed to determine the appropriate leaching conditions. In addition, ultrasound was employed as an enhancement method during the leach, since recent studies have shown that the use of ultrasound accelerates the dissolution of metals [22] and REEs, achieving nearly 100% in 1 to 3 h [23][24][25]. In sonochemistry, molecules undergo chemical reactions promoted by the application of ultrasound radiation (20 kHz-10 MHz) in solid-liquid systems; ultrasound enhances the diffusion of soluble species in the liquid phase and increases the rate of penetration into the solid principally by the cavitation effect, which leads to the creation of many microcracks on the solid surface.…”
Section: Introductionmentioning
confidence: 99%
“…A thermodynamic study, in the form of species distribution diagrams using the Hydra-Medusa software suite [21] was performed to determine the appropriate leaching conditions. In addition, ultrasound was employed as an enhancement method during the leach, since recent studies have shown that the use of ultrasound accelerates the dissolution of metals [22] and REEs, achieving nearly 100% in 1 to 3 h [23][24][25]. In sonochemistry, molecules undergo chemical reactions promoted by the application of ultrasound radiation (20 kHz-10 MHz) in solid-liquid systems; ultrasound enhances the diffusion of soluble species in the liquid phase and increases the rate of penetration into the solid principally by the cavitation effect, which leads to the creation of many microcracks on the solid surface.…”
Section: Introductionmentioning
confidence: 99%
“…A thermodynamic study, in the form of species distribution diagrams using the Hydra-Medusa software suite [21] was performed to determine the appropriate leaching conditions. In addition, ultrasound was employed as an enhancement method during the leach, since recent studies have shown that the use of ultrasound accelerates the dissolution of metals [22] and REEs, achieving nearly 100% in 1 to 3 h [23][24][25]. In sonochemistry, molecules undergo chemical reactions promoted by the application of ultrasound radiation (20 kHz-10 MHz) in solid-liquid systems;…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ultrasound was employed during the leach as complementary method. Recent studies have shown that the use of ultrasound accelerates the dissolution of metals [22] and rare earth elements, achieving nearly 100% in 1 to 3 hours [23][24][25]. In sonochemistry, molecules undergo a chemical reaction promoted by the application of ultrasound radiation (20 kHz -10 MHz) in solid-liquid systems; ultrasound enhances the diffusion of soluble species in the liquid phase and increases the rate of penetration into the solid principally by the cavitation effect, which leads to the creation of many microcracks on the solid surface.…”
Section: Introductionmentioning
confidence: 99%